Translation and Psychometric Testing of the Indonesian Version of the Preparedness for Caregiving Scale - Ike Wuri Winahyu Sari; Novita Nirmalasari (Faculty of Nursing, Universitas Jember, 2021)
Background: Although many previous studies have used the Preparedness for Caregiving Scale (PCS), it has not been translated and validated in Indonesia. Purpose: This study aimed to translate and evaluate the PCS’s psychometric adequacy among family caregiver of non-communicable disease (NCD) patients in Indonesia. Methods: The linguistic of the PCS was validated using a standard forward-backward process. The Indonesian version was approved with Content Validity Index (CVI). Then a cross-sectional survey was conducted to establish the construct validity of the PCS to measure caregiver preparedness. A purposive sampling approach was used to recruit 40 consenting family caregivers of NCD patients. The PCS sum score was correlated with each item using Pearson product-moment. The internal consistency of the Indonesian version of the PCS (I-PCS) was assessed using Cronbach’s alpha. Results: The Item-CVI (I-CVI) and Scale-level CVI (S-CVI) of the I-PCS were 1.00. It showed the high content validity of the I-PCS. The I-PCS revealed a Cronbach’s alpha of 0.933 for the total score. The Pearson-r was more than 0.320 indicated that the item valid. Conclusion: The I-PCS is appeared to be valid and reliable for measuring the caregiver preparedness of NCD patients in Indonesia.